Metode Natural Feature Tracking dan Fast Corner Detection dengan Teknik Virtual Button Pada Aplikasi Sistem Pernafasan Manusia - Rifqi Naufal Senja Pratama; Fauziah Fauziah; Ratih Titi Komala Sari (STMIK Budi Darma, 2021)
At this time the development of information and communication technology has developed very rapidly. As in smartphones, the technology contained in smartphones today has an important role for human activities. The technology that is currently being implemented on smartphones is Augmented Reality. Augmented reality can be used in all fields of human activity, one of which is in the field of education. The purpose of this research is to develop an educational media about the organs of the human respiratory system that is interactive and can be understood by users such as students. In this study, 2 methods were used, namely Fast Corner Detection and Natural Feature Tracking Methods to read a marker which would later bring up information and also use the virtual button technique in the application. In testing using 5 smartphones. The results of testing at an angle of 60o and 90o the five smartphones can detect markers. The distance test has different results from the smallest having a minimum distance of ±70 cm to a maximum distance of ±150 cm. In tests based on light intensity, the five smartphones can detect markers at light intensities above 5 lux